Bronchial airway gene expression in smokers with lung or head and neck cancer. (4th February 2014) - Van Dyck, Eric; Nazarov, Petr V.; Muller, Arnaud; Nicot, Nathalie; Bosseler, Manon; Pierson, Sandrine; Van Moer, Kris; Palissot, Valérie; Mascaux, Céline; Knolle, Ulrich; Ninane, Vincent; Nati, Romain; et al.
Abstract Cigarette smoking is the major cause of cancers of the respiratory tract, including non‐small cell lung cancer (NSCLC) and head and neck cancer (HNC). In order to better understand carcinogenesis of the lung and upper airways, we have compared the gene expression profiles of tumor‐distant, histologically normal bronchial biopsy specimens obtained from current smokers with NSCLC or HNC (SC, considered as a single group), as well as nonsmokers (NS) and smokers without cancer (SNC). RNA from a total of 97 biopsies was used for gene expression profiling (Affymetrix HG‐U133 Plus 2.0 array). Differentially expressed genes were used to compare NS, SNC, and SC, and functional analysis was carried out using Ingenuity Pathway Analysis (IPA). Smoking‐related cancer of the respiratory tract was found to affect the expression of genes encoding xenobiotic biotransformation proteins, as well as proteins associated with crucial inflammation/immunity pathways and other processes that protect the airway from the chemicals in cigarette smoke or contribute to carcinogenesis. Finally, we used the prediction analysis for microarray (PAM) method to identify gene signatures of cigarette smoking and cancer, and uncovered a 15‐gene signature that distinguished between SNC and SC with an accuracy of 83%. Thus, gene profiling of histologically normal bronchial biopsy specimens provided insight into cigarette‐induced carcinogenesis of the respiratory tract and gene signatures of cancer in smokers.